The Impact of New Media Marketing, Information Credibility, and Customer Satisfaction on Brand Loyalty in The Publishing Industry - Yuan, Wenke; Traiwannakij, Surachai (Economics and Business International Conference Proceeding, 2024)
This study takes publishing companies as an example to explore the impact of new media marketing, information credibility, and customer satisfaction on Brand Loyalty. Using quantitative research methods and various statistical methods, including descriptive analysis, correlation analysis, and regression analysis, to examine the relationship between demographic variables, new media marketing, information credibility, and customer satisfaction with Brand Loyalty. Finally, based on these findings, some suggestions are provided. The results of this study provide theoretical support for publishing companies to develop effective marketing strategies in the digital era. By focusing on key factors such as new media marketing, information credibility, and customer satisfaction, publishing companies can enhance Brand Loyalty and achieve sustainable development.